Integrated and scalable augmented reality multiplayer robotic platform - Tandianus, Budianto (2020)
We propose a scalable AR (Augmented Reality) multiplayer robotic platform, which enables multiple players to control different machines (a drone and a robot) in shared environments, i.e virtual and real environments. We use state-of-theart visual SLAM (Simultaneous Localization and Mapping) algorithms for tracking machine poses based on camera and IMU (Inertial Measurement Units) inputs. Players will observe consistent AR objects between them thanks to our backend system, which synchronizes the AR objects between players. Moreover, the system is scalable in term of hardware (e.g. IMU, camera, machine type) and software (SLAM algorithm) as we utilize ROS for communication between modules. We demonstrate our system on a game developed in Unity, a robust and widely used popular game engine. We present some statistics of the game such as its frames-per-second performance.